THE INFLUENCE OF DIGITAL LITERACY AND ENTREPRENEURIAL ORIENTATION ON BUSINESS DECISION MAKING AMONG DIGITAL MSMES IN BATAM CITY - Muhammad Haldy; Hikmah Hikmah; Risca Azmiana (JIM UPB (Jurnal Ilmiah Manajemen Universitas Putera Batam), 2025)
The rapid development of digital technology has encouraged Micro, Small, and Medium Enterprises (MSMEs) to adapt their business activities, particularly in the process of business decision-making. Digital literacy and entrepreneurial orientation are important factors that influence the quality of business decisions in digital MSMEs. This study aims to analyze the effect of digital literacy and entrepreneurial orientation on business decision-making among digital MSMEs in Batu Aji District. This research employs a quantitative approach using a survey method involving 100 digital MSME owners as research respondents. Data were collected through structured questionnaires and analyzed using multiple linear regression techniques. The results indicate that digital literacy has a positive and significant effect on business decision-making. Entrepreneurial orientation also has a positive and significant effect on business decision-making. Simultaneously, digital literacy and entrepreneurial orientation significantly influence business decision-making among digital MSMEs in Batu Aji District. These findings suggest that improving digital literacy and strengthening entrepreneurial orientation play a crucial role in supporting more effective and strategic business decision-making. This study is expected to provide insights for MSME actors and policymakers in formulating strategies and programs for the development of digital MSMEs at the district level.